MODELAGEM E SIMULACÃO COMPUTACIONAL DE TEORIA QÂNTICA ORCH OR - Martins, Mirkos Ortiz (2018)
The realization of quantum computers has been investigated from the point of view of theoretical and experimental diferent approaches such as electronic spins; trapped ions, nuclear magnetic resonance, etc. A alternative approach is being discussed in the eld of biological quantum computing: a quantum nanomachine of Penrose and Hamero model known as Orch OR (Orchestrated Objective Reduction). The nanomachine is based on the quantum behavior of brain microtubules. Microtubules are structures biological existing inside the nerve cells that form dimers of polarized proteins, called tubulin, with globular shape, which behave as qubits. The behavior of microtubules led to an interesting aspect of the model Orch Or call objective reduction. Essentially, the objective reduction is the idea that quantum systems that isolates the external environment will reduce (or collapsing) because of their intrinsic geometrical characteristics. Understanding the behavior of microtubules may provide us a more accurate view of how it handled the information sent to the brain by electrical impulses through sensory system and how physical consciousness is created. In this work, presents a modeling and simulation for computational quantum of biological nanomachines Penrose and Hamero. More specically, it discusses a computational model for the nanomachine by use of the cellular automata. The simulation of this model is implemented graphically in the functional programming language Haskell. Haskell is a functional language (high level) and pure already has been studied in several papers as an interesting language for modeling and simulation of quantum structures. Through the use of computer simulation can be veried interesting properties the behavior of tubulin, such as conformational changes in series (planar and stationary waves) and conformational change of quantum states (unknown of state value). The model for understanding the point of view of a simple computational microtubular give a basis for future work, based on this model and is intended to develop algorithms for a simulated microtubules in Haskell. This dissertation aims to give subsidies to simulate neural activities more complex future.